Perancangan Dokumen Hazard Identification, Risk Assessment, Risk Control (HIRARC) di PT Anugerah Rimba Raya - Teddy Soeyono; Kriswanto Widiawan (Jurnal Titra, 2021)
PT Anugerah Rimba Raya is a wood processing company that doesn’t have work hazard identification document. The company’s previous accidents report showed that there were 19 accidents that occurred from 2018 to 2020. The design of the HIRARC document aims to identify the types of hazards that can occur in the work environment, to evaluate the magnitude of the risks and its impacts, and to document the efforts of hazard control in order to minimize hazard potential. The source of data collected during hazard identification stage will be carried out by direct observation, crew interviews, and company’s previous accident record. Futhermore, at the risk assessment stage, 2 parameters will be used, probability and severity. The assessment stage will divide hazard risk into different levels which is extreme risk, high risk, medium risk, low risk. After that, the risk control will be carried out based on the control hierarchy which is divided into elimination, substitution, technical design, administrative control, personal protective equipment. The prediction result of reduction risk levels after proposed controls showed a decrease in the level of risk that existed before.